Synergy Against the Prevention of Terrorism and Understanding Radicalism - Muin, Fatkhul; Aspihanto, Aan (Law Research Review Quarterly, 2017)
This study analyzes a comprehensive perspective on efforts to prevent terrorism and spread radicalism in Indonesia. Terrorist movements are an issue of primary concern for all elements / steakholders in Indonesia. The handling of these crimes often causes problems in society, with such conditions, it is necessary to prevent efforts to prevent terrorism and understand radicalism which often causes anxiety in the community due to theoretical actions and the spread of radicalism, especially to the younger generation. In efforts to prevent terrorism and radicalism, all elements must be involved. The existence of Law of the Republic of Indonesia Number 9 of 2013 concerning Prevention and Eradication of Criminal Funding of Terrorism and Presidential Regulation Number 12 of 2012 concerning Amendments to Presidential Regulation Number 46 of 2010 concerning Terrorism Prevention Agency, institutionally, prevention and non-criminal acts of terrorism can be carried out by state apparatus, but in other aspects active involvement of the community towards the prevention of terrorism and radical understanding in society is needed, because with the active involvement of the community, the level of spread of radical branches and public awareness of the dangers of terrorism for the social life of the community. This study aims to explore the need for synergy of all stakeholders in the prevention of terrorism and the spread of radicalism. This study uses a normative approach.